1998
DOI: 10.1200/jco.1998.16.12.3788
|View full text |Cite
|
Sign up to set email alerts
|

Burkitt-like lymphomas in AIDS patients: characterization within a series of 103 human immunodeficiency virus-associated non-Hodgkin's lymphomas. Burkitt's Lymphoma Study Group.

Abstract: BLL is a frequent entity among AIDS lymphomas and should be considered as a morphologic variant of BL in the context of severe immunodepression that occurs in HIV-infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
1
8

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(64 citation statements)
references
References 0 publications
0
55
1
8
Order By: Relevance
“…13 Patients with HIV-BL closely resemble the general BL population in terms of stage, marrow involvement (33% to 35%), CNS involvement (17% to 19%), 14 and histology. 15 Prior to HAART, combination chemotherapy was less successful for patients with HIV-associated NHL than for HIV-negative patients with similar NHL histopathology. Early deaths were often the result of opportunistic infection.…”
Section: Introductionmentioning
confidence: 99%
“…13 Patients with HIV-BL closely resemble the general BL population in terms of stage, marrow involvement (33% to 35%), CNS involvement (17% to 19%), 14 and histology. 15 Prior to HAART, combination chemotherapy was less successful for patients with HIV-associated NHL than for HIV-negative patients with similar NHL histopathology. Early deaths were often the result of opportunistic infection.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of 75 adults with BL (46 HIV-positive) found no difference between HIV-positive and HIV-negative patients in terms of disease stage, BM (33-35%) and CNS (17-19%) involvement, 14 and histology. 15 The optimal treatment for adult patients with HIV-associated BL is not clear. In the era before highly active antiretroviral therapy (HAART), combination chemotherapy was less successful for patients with HIV-associated NHL than for HIV-negative patients with similar NHL histopathology.…”
mentioning
confidence: 99%
“…In contrast with the African tumors in jaw, maxilla and orbital bones, this sporadic form involving the abdomen, typically the ileocecal region, and rarely involving orbital or ocular structures 10 . Originally the BL immunocompromised variant was described in patients with AIDS [11][12][13] . The infection by Epstein-Barr virus has been implicated in BL, being positive in 20% of sporadic cases, 40% in cases and as high as 95% in the endemic form [9][10][11] .…”
Section: Discussionmentioning
confidence: 99%
“…Originally the BL immunocompromised variant was described in patients with AIDS [11][12][13] . The infection by Epstein-Barr virus has been implicated in BL, being positive in 20% of sporadic cases, 40% in cases and as high as 95% in the endemic form [9][10][11] . One large study has reported that cases with positive Epstein-Barr antibody had better outcomes [11][12] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation